Oncogene amplification during tumorigenesis of established rat fibroblasts reversibly transformed by activated human ras oncogenes. - Winter, E (1986)
Normal rat fibroblasts of the established cell line Rat 4 were cotransformed with activated human ras oncogenes and with a cloned chicken thymidine kinase (tk) gene. Linkage between tk and ras genes allowed the isolation of oncogene deletion revertants and of cell clones showing varying degrees of malignant phenotype. Southern and Northern experiments in concert with tumorigenicity assays show that the malignant transformation of these cells by mutant ras oncogenes is a gradual but reversible process that depends on the relative abundance of oncogene sequences and their corresponding transcripts. We also show that moderate amplification of a c-K-ras oncogene in these cells results in a clear increase in their tumorigenicity and that the mutant gene present in low copy numbers in cultured cells undergoes amplification in the corresponding in vivo induced tumors.